STUDENTS OF THE 21ST CENTURY: NAVIGATING EDUCATION IN A TECHNOLOGICAL AGE - Egamberdiyeva Irodaxon; Yuldsheva Mehriyo; Mamatursunova Marxaboxon (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Abstract: The 21st century has brought about a paradigm shift in the way students learn, interact, and engage with education. This article explores the multifaceted impact of technology on the students of this era, highlighting both the opportunities and challenges they face. It delves into the influence of digital tools, the changing dynamics of social interactions, and the evolving educational landscape, considering how these factors have shaped the experiences and mental well-being of students. Drawing insights from current literature and scholarly research, this article seeks to provide a comprehensive understanding of the modern student and the complex interplay between technology and mental health.